Cryptogenic Stroke with a Patent Foramen Ovale: Medical Therapy, Percutaneous Intervention, or Surgery. Issue 3 (19th January 2016) - Bedeir, Kareem; Volpi, John; Ramlawi, Basel
ABSTRACT : More than one third of ischemic strokes have an unidentifiable cause. Patent foramen ovale (PFO) plays a controversial role in this subset of patients. The evidence for and against the hypothesis of paradoxical embolism is reviewed and we discuss the optimal management of a PFO under different circumstances. doi: 10.1111/jocs.12693 (J Card Surg 2016;31:156–160)